2018
DOI: 10.4103/ijccm.ijccm_24_18
|View full text |Cite
|
Sign up to set email alerts
|

The era of device colonizers:Chryseobacterium indologenesinfections from a tertiary care center in North India

Abstract: Background:Chryseobacterium indologenes is a hospital environment contaminant and can cause healthcare-associated infections.Methods:Patients with C. indologenes infections in a tertiary care center in North India for 6 months were evaluated for susceptibility patterns, comorbidities, mechanical devices, risk factors, and treatment outcomes. The organism was provisionally identified phenotypically, and identification was confirmed by the BD Phoenix automated microbiology system. Minimum inhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…C. indologenes is easily distinguished from other nonfermenters by its individual ability to produce indole. 6 In the present study, 9 isolates of C. indologenes were recovered from various samples like ascitic fluid, respiratory secretions and urine which were correlated with the study conducted by Kaur H et al 2 and Vidhi Jain et al 7 The isolate of C. indologenes from ascitic fluid was from a chronic liver disease patient and it was accounted as a true pathogen. Most of the other isolates were from ward patients in this study.…”
Section: Discussionsupporting
confidence: 83%
“…C. indologenes is easily distinguished from other nonfermenters by its individual ability to produce indole. 6 In the present study, 9 isolates of C. indologenes were recovered from various samples like ascitic fluid, respiratory secretions and urine which were correlated with the study conducted by Kaur H et al 2 and Vidhi Jain et al 7 The isolate of C. indologenes from ascitic fluid was from a chronic liver disease patient and it was accounted as a true pathogen. Most of the other isolates were from ward patients in this study.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the result is also in agreement with the result obtained by Chen et al (2013), who evaluated the antimicrobial susceptibility of 113 C. indologenes isolates obtained from 2004 to 2011 and found that 34.4% were susceptible to levofloxacin. Moreso, previous studies carried out by Jain et al (2018) also reported the susceptibility of C. indologenes to levofloxacin to be 98%.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, there was no correlation between the dominant microbiota and the actual bacteremic pathogens. Previously, Bacillus and Flavobacterium have been reported as causes of device-related BSI in patients with signi cant underlying conditions [15][16][17][18][19][20][21][22]. Speci c bacteria such as Arthrobacter, SMB53, Dyella, Paracoccus, and Pedobacter have been reported as dialysis catheter-related infections or CRBSI [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%